2009
DOI: 10.1093/pubmed/fdp049
|View full text |Cite
|
Sign up to set email alerts
|

Functional health literacy among primary health-care patients: data from the Belgrade pilot study

Abstract: These results provide evidence that limitations in functional health literacy are widespread among primary health-care patients and encourage efforts for further monitoring. Low health literacy may impair a patient's understanding of health messages and limit their ability to attend to their medical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
40
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 12 publications
19
40
4
4
Order By: Relevance
“…An admittedly speculative explanation could be that the communication between physician and patients with lower educational background is to some degree ineffective in spite of more intense contacts. This would support the relevance of the relatively new concept of health literacy (Jovic-Vranes et al 2009). Especially, the concept of health literacy in this context merits further research.…”
Section: Discussionsupporting
confidence: 57%
“…An admittedly speculative explanation could be that the communication between physician and patients with lower educational background is to some degree ineffective in spite of more intense contacts. This would support the relevance of the relatively new concept of health literacy (Jovic-Vranes et al 2009). Especially, the concept of health literacy in this context merits further research.…”
Section: Discussionsupporting
confidence: 57%
“…The similar finding was also reported by Tokuda et al 27 On the other hand there are studies showing a decrease of Health Literacy level as the age increases. 28,29 It could be speculated that the reason behind the different findings of these studies were caused by the disparities of the age and occupations.…”
Section: Discussionmentioning
confidence: 96%
“…Third, being unable to work was also a significant predictor of being at risk for low health literacy in both univariate and multivariable models. A study conducted in Serbia found that employment status (employed vs. other) was significantly associated with health literacy (Jovic-Vranes, Bjegovic-Mikanovic, & Marinkovic, 2009). The same study also found that the number of chronic conditions was significantly associated with health literacy (Jovic-Vranes, Bjegovic-Mikanovic, & Marinkovic, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Serbia found that employment status (employed vs. other) was significantly associated with health literacy (Jovic-Vranes, Bjegovic-Mikanovic, & Marinkovic, 2009). The same study also found that the number of chronic conditions was significantly associated with health literacy (Jovic-Vranes, Bjegovic-Mikanovic, & Marinkovic, 2009). Although reasons for being unable to work may have included being disabled or having significant health concerns in the current study, we did not collect specific reasons that individuals might have been unable to work which may have further informed these findings.…”
Section: Discussionmentioning
confidence: 99%